Dynamic Policy Sabotage. Issue 3 (17th April 2021) - Gieczewski, Germán; Li, Christopher
Abstract: A common feature of democratic politics is that the opposition may sabotage the implementation of policies put forth by the incumbent party. This paper presents a theoretical analysis of the opposition's optimal use of sabotage and of how the prospect of sabotage conditions the incumbent's agenda. We show that, when a proposed policy enjoys moderate public support, the incumbent will attempt to pass it as early as possible, and the opposition will exert increasing effort to sabotage it as the next election approaches. In contrast, the incumbent delays the passage of highly popular policies until near the end of her term, and these are not subject to sabotage. Finally, the threat of sabotage persuades the incumbent to abandon unpopular proposals. In extensions, we show how our results compare under different electoral institutions, and how legislative obstruction can be used as an alternative or complement to sabotage.